Relationship between subjective wellbeing and weight perception in children and adolescents: Gender and age differences - Gaspar, Tania (2016)
The relation between weight status (Body Mass Index - BMI), weight perception and subjective wellbeing remains unclear. Several studies conclude that discrepancies can be found between weight status and weight perception, among children and adolescents. The present study aims at investigating the associations between subjective wellbeing and individual characteristics, among children and adolescents. The sample included 1200 children and adolescents (51.7 % girls, aged 9 to 17). Their mean age was 12.55 years (SD = 1.61). The questionnaire was completed in school context, asking about the subjective wellbeing, use of self-regulation, eating behavior awareness/care, weight perception and sociodemographic questions such as age, gender and BMI. The study found a strong association between BMI and weight perception, although subjective wellbeing was better explained by weight perception than by BMI. Eating awareness and self-regulation also played an important role in subjective controlling for age and gender. Age and gender interfere in the relation between subjective wellbeing and other variables. The multiple regression model is more robust and explicative for girls and older children. Psychological factors related to weight, such as weight perception, self-regulation and eating awareness have a stronger explicative impact in subjective wellbeing compared to physical aspects, such as Body Mass Index. The relation between subjective wellbeing and weight is influence by age and gender.